Enhancing Customer and Supplier Relationship through the Iterative Customer Relationship Management Process - Hasbullah Ashari; Azizah Ahmad; Hussein Abdou Al-Homery (International Journal of Supply Chain Management, 2019)
CRM Process is considered the main critical success factor of CRM systems implementations, so special care should be given for each and every process in the organization supply chain for goal achievements.This paper provides an extensive review of the etiquette regarding the CRM processes. This review aims to increase the understanding of the different perspectives, levels of CRM processes, and CRM process models.The CRM Process either macro process or micro process. On the macro level, we consider merging Knowledge Management (KM) with Customer Relationship Management (CRM) to have Customer knowledge Management (CKM) to reduce the risk of relationship failure and customer intelligence for the profitability of the organization supply chain. The knowledge management process starts with data collection, followed by intelligence generation and eventually, intelligence dissemination as an iterative process. On the other side the Micro-level process (Interaction Management) where its quality determined by Consistency, Relevancy, and Appropriateness. In the same context, other scholars classified the CRM process into three levels: (Customer facing level, The Functional level, and the Companywide level (Customer-oriented CRM process). Then, in the article, we are going to demonstrate the CRM process models and the proposed Iterative CRM process model by the author.